2022
DOI: 10.1101/2022.11.24.22282735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity and durability against Omicron BA.1, BA.2 and BA.4/5 variants at 3 to 4 months after a heterologous COVID-19 booster vaccine in healthy adults with a two-doses CoronaVac vaccination

Abstract: Objectives: Several countries have authorized a booster vaccine campaign to combat the spread of COVID-19. Data on persistence of booster vaccine-induced immunity against new Omicron subvariants are still limited. Therefore, our study aimed to determine the serological immune response of COVID-19 booster after CoronaVac-priming. Methods: A total of 187 CoronaVac-primed participants were enrolled and received an inactivated (BBIBP), viral vector (AZD1222) or mRNA vaccine (full-/half-dose BNT162B2, full-/half-do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…We observed sustained detectable immunogenicity through 3-month post-third boost, although a decline in antibody response was observed in all vaccination regimens. This finding corroborates a previously conducted study 7 that reported on the durability of the immune response at 3 months after booster vaccination in participants who received either an adenoviral-vector or mRNA vaccine as a third dose following two doses of CoronaVac vaccines. Additionally, a previous report 13 has summarized the benefits of heterologous vaccination with primary series and/or booster doses, showing a better immune response than homologous vaccination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed sustained detectable immunogenicity through 3-month post-third boost, although a decline in antibody response was observed in all vaccination regimens. This finding corroborates a previously conducted study 7 that reported on the durability of the immune response at 3 months after booster vaccination in participants who received either an adenoviral-vector or mRNA vaccine as a third dose following two doses of CoronaVac vaccines. Additionally, a previous report 13 has summarized the benefits of heterologous vaccination with primary series and/or booster doses, showing a better immune response than homologous vaccination.…”
Section: Discussionsupporting
confidence: 92%
“… 5 , 6 However, only a few studies have reported on the longitudinal immune response after the heterologous booster dose. 5 , 7 , 8 Additionally, this coincided with the emergence of new omicron subvariants, which highly evade immunity, raising concerns about the durability of the immune response after the third dose booster and its cross-reactivity in neutralizing the omicron subvariant.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the immunity provided by other mRNA boosters against omicron variants can last for up to 4 months. 32 To better understand the public health implications of RQ3013 as a booster, we are following study participants for at least six months to monitor immunity and evidence of vaccine failures, and plan to report on humoral immunity assays in forthcoming studies. Fourth, the generalizability of our conclusion may be constrained due to the high prevalence of prior SARS-CoV-2 infections in the current population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to evaluate the SARS-CoV-2 Spike 1-specific immunoglobulin A (anti-S1 IgA) by using the leftover serum from our previous cohort studies on the safety and immunogenicity of COVID-19 vaccines [ 15 , 16 , 17 , 18 , 19 , 20 ]. In our previous studies, we reported the levels of binding antibodies, such as IgG, and neutralizing antibodies, following immunization with different regimens of two, three, and four doses of COVID-19 vaccines.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we reported the levels of binding antibodies, such as IgG, and neutralizing antibodies, following immunization with different regimens of two, three, and four doses of COVID-19 vaccines. The study was conducted at the Center of Excellence in Clinical Virology, Faculty of Medicine, Chulalongkorn University in Bangkok, Thailand between March 2021 and September 2022 [ 15 , 16 , 17 , 18 , 19 , 20 ]. The participants were conveniently assigned to receive any vaccine that was available during the study period.…”
Section: Methodsmentioning
confidence: 99%